Nivel de ventas del local comercial “Punto Cell” del cantón Ventanas - Cordero Muñoz, Briggitte Marilin (2020)
The present case study carried out in the company “Punto Cell” has a production focus, for which reason it is based on the sales levels that it has had on cell phones from 2016 to 2019, due to that during this period its sales have decreased by a considerable percentage, which is not encouraging for the company. The objective of this research is to externalize and understand the causes of the sales levels presented by the company and the various factors that influence it both externally and internally